Comparative study of the gasification of coal and its macerals and prediction of the synergistic effects under typical entrained-bed pulverized coal gasification Conditions - Jiang, Peng; Guo, Dengting; Luo, Xiang; Xu, Mengxia; Wu, Tao (2019)
This research is focused on the gasification performance of coal and its corresponding macerals as well as on the interactions among macerals under typical gasification conditions by Aspen Plus modeling. The synergistic coefficient was employed to show the degree of interactions, while the performance indicators including specific oxygen consumption (SOC), specific coal consumption (SCC), cold gas efficiency (CGE), and effective syngas (CO + H2) content were used to evaluate the gasification process. Sensitivity analyses showed that the parent coal and its macerals exhibited different gasification behaviors at the same operating conditions, such as the SOC and SCC decreased in the order of inertinite > vitrinite > liptinite, whereas CGE changed in the order of liptinite > vitrinite > inertinite. The synergistic coefficients of SOC and SCC for the simulated coals were in the range of 0.94–0.97, whereas the synergistic coefficient of CGE was 1.05–1.13. Moreover, it was found that synergistic coefficients of gasification indicators correlated well with maceral contents. In addition, the increase in temperature was found to promote the synergistic coefficients slightly, whilst at an oxygen to coal mass ratio of 0.8 and a steam to coal mass ratio of 0.8, the highest synergistic coefficient was obtained.